A comparative analysis of differentially expressed genes in rostral and caudal regions after spinal cord injury in rats - Xue-Min Cao; Sheng-Long Li; Yu-Qi Cao; Ye-Hua Lv; Ya-Xian Wang; Bin Yu; Chun Yao (Neural Regeneration Research, 2022)
The initial mechanical damage of a spinal cord injury (SCI) triggers a progressive secondary injury cascade, which is a complicated process integrating multiple systems and cells. It is crucial to explore the molecular and biological process alterations that occur after SCI for therapy development. The differences between the rostral and caudal regions around an SCI lesion have received little attention. Here, we analyzed the differentially expressed genes between rostral and caudal sites after injury to determine the biological processes in these two segments after SCI. We identified a set of differentially expressed genes, including Col3a1, Col1a1, Dcn, Fn1, Kcnk3, and Nrg1, between rostral and caudal regions at different time points following SCI. Functional enrichment analysis indicated that these genes were involved in response to mechanical stimulus, blood vessel development, and brain development. We then chose Col3a1, Col1a1, Dcn, Fn1, Kcnk3, and Nrg1 for quantitative real-time PCR and Fn1 for immunostaining validation. Our results indicate alterations in different biological events enriched in the rostral and caudal lesion areas, providing new insights into the pathology of SCI.